Cognitive and Intelligence Development: A Systematic Literature Review - Dessy Syofiyanti; Hasnida Hasnida (Jurnal Inovasi Pendidikan dan Sains, 2025)
The cognitive and intelligence development represents two crucial aspects in child developmental psychology that play an important role in shaping thinking skills, problem-solving abilities, and adaptability to the environment. This study aims to identify, examine, and synthesize the main findings from national and international scientific literature published between 2021 and 2025 related to the cognitive and intelligence development in school-aged children. The method used was a Systematic Literature Review (SLR), which involved screening 120 articles from the Scopus, Web of Science, ERIC, ScienceDirect, and Google Scholar databases. This resulted in 10 articles that met the inclusion criteria for further analysis. The analysis results indicate that the development of children's cognition and intelligence is affected by three main dimensions: direct instructional interventions, external environmental factors, and theory-based pedagogical approaches. Holistic and integrative learning approaches have been shown to have a significant effect on optimizing children's intellectual capacity. The conclusion of this review highlights the importance of synergy among education, health, and the social environment in designing effective and sustainable learning strategies to support children's cognitive development. Further research using longitudinal approaches is recommended to assess the long-term effects of various implemented interventions